Making sense of adversarial interpreting - Kredens, Krzysztof (Language and Law / Linguagem e Direito, 2017)
This article makes an ontological case for ‘adversarial interpreting’, which occurs in contexts where an interpreter’s output is monitored and/or challenged, either during the speech event or subsequently, by another interpreter or individual with knowledge of both languages. In the absence of studies with a specific focus on the phenomenon, the paper introduces adversarial interpreting as a problem in its own right and sets out to answer the question of how the presence of two interpreters, or an interpreter and a monitoring participant, in the same speech event impacts on the communication process. The discussion is informed by the findings of a study based on the analysis of the transcript of an interpretermediated police interview and input from practising interpreters with experience of adversarial interpreting. The findings indicate that adversarial interpreting can impact the communication process negatively, but can also help ensure accuracy.